The role of the testa during the establishment of physical dormancy in the pea seed - Janská, Anna; Pecková, Eva; Sczepaniak, Bogna; Smýkal, Petr; Soukup, Aleš (Annals of botany, 2019)
BACKGROUND: A water-impermeable testa acts as a barrier to a seed's imbibition, thereby imposing dormancy. The physical and functional properties of the macrosclereids are thought to be critical determinants of dormancy; however, the mechanisms underlying the maintenance of and release from dormancy in pea are not well understood. METHODS: Seeds of six pea accessions of contrasting dormancy type were tested for their ability to imbibe and the permeability of their testa was evaluated. Release from dormancy was monitored following temperature oscillation, lipid removal and drying. Histochemical and microscopic approaches were used to characterize the structure of the testa. KEY RESULTS: The strophiole was identified as representing the major site for the entry of water into non-dormant seeds, while water entry into dormant seeds was distributed rather than localized. The major barrier for water uptake in dormant seeds was the upper section of the macrosclereids, referred to as the 'light line'. Dormancy could be released by thermocycling, dehydration or chloroform treatment. Assays based on either periodic acid or ruthenium red were used to visualize penetration through the testa. Lipids were detected within a subcuticular waxy layer in both dormant and non-dormant seeds. The waxy layer and the light line both formed at the same time as the establishment of secondary cell walls at the tip of the macrosclereids. CONCLUSIONS: The light line was identified as the major barrier to water penetration in dormant seeds. Its outer border abuts a waxy subcuticular layer, which is consistent with the suggestion that the light line represents the interface between two distinct environments - the waxy subcuticular layer and the cellulose-rich secondary cell wall. The mechanistic basis of dormancy break includes changes in the testa's lipid layer, along with the mechanical disruption induced by oscillation in temperature and by a decreased moisture content of the embryo.
Keywords: semena rostlinná; voda; Temperature; hrách setý; Pisum sativum; Plant Dormancy; Germination; teplota; Water; Seeds; vegetační klid; klíčení